Sugar-Related Claims, Perceived Healthfulness, and Brand Trust: Predicting Ready-to-Drink Tea Purchase - Jevica, Jevica; Haposan Pangaribuan , Christian (Pelopor Publikasi Akademika, 2024)
The purpose of this study is to understand how claims related to sugar content in products affect consumer perception of product health (perceived healthfulness), brand trust, and intention to buy the product (likelihood to purchase). The method used in this study is to use an experimental research design with hypothesis testing. The research method used was a survey with a questionnaire distributed to respondents in Jabodetabek who had bought and consumed ready to drink tea in the last three months. The analysis was carried out by the SEM method using the Smart PLS program. The results of this study show that claims related to sugar content in products have a positive and significant influence on perceived healthfulness and consumer trust in brands (brand trust). Claims that the product has a healthier sugar content can directly increase consumer purchase interest (likelihood to purchase). In addition to direct influence, these claims influence buying interest through a mediation mechanism of health perception and brand trust, strengthening the overall effect on consumers’ purchasing decisions. This study emphasizes the importance of considering the role of mediation in understanding how product claims affect consumer behavior.